Wonders of weather [motion picture]. (Discovery Communications, LLC, 2011)
Disc. 1. We use satelites, planes, computers and butterflies to predict the weather, but we're still not accurate. Learn what all those signs on the TV weather charts mean). 2. Deserts (Why are large regions of the Earth covered by deserert, and how do people adapt to living in these harsh conditions? In the mid-1930s, drought vturned America's midsection into a dustbowl. Prolonged droughts have dried up Sub-Saharan Africa and hit places like Ethiopia hardest. What are the economic and social consequencies? Look at recent efforts to seed clouds to trigger rainfall. Does it work? (50 mins)